Use of electrotechnology processing biomass and burning depleted hydrocarbon mixtures to ensure carbon neutrality - Zablodsky, M.; Schvorov, S.; Trokhanyak, V.; Andrievsky, A.; Koval, E. (Energy and Automation, 2024)
Proposed technological structures using electrotechnology for biomass processing and burn of depleted hydrocarbon mixtures to provide carbon neutrality. An innovative energy supply scheme is built in the system of processing of poultry products into fertilizers, feed and fuel. The identified parameters of emissions in experimental studies of the processes of burning of traditional fuel and fuel with the addition of activated water in the combustion chamber of combustion of internal combustion motors for the developed technological structure of the multi-ripening of the combustion of the burning of the stehiometric drying of the billow-depleted air-air-water. The proposed structure of the investment distribution distribution system between low carbon energy technologies, as well as an expression that can be evaluated by carbon emissions during biomass processing processes and burning of depleted hydrocarbon mixtures, taking into account the number of carbon emissions during collection, processing and transportation processes three -component fuel mixtures.Key words: multifunctional electromechanical converter, rotary magnetic field, pyrolysis, combustible gas, biovur, multifaceted pulse discharges